2011
DOI: 10.1038/jid.2011.28
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Histone H2AX Is a Powerful Tool for Detecting Chemical Photogenotoxicity

Abstract: Several light-absorbing chemicals are known to show phototoxic effects involving many kinds of DNA damage, and are suspected of initiating skin cancer. In this study, we clarified that phosphorylated histone H2AX (γ-H2AX) (phosphorylated histone H2AX), which was produced with the induction of DNA double-strand breaks, is a sensitive photogenotoxic marker. The immortal human keratinocyte line HaCaT was treated with a library of 11 chemicals (including known strong and weak phototoxic chemicals, and nonphototoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 49 publications
1
35
0
2
Order By: Relevance
“…The repair of these types of damage also induce c-H2AX (Bonner et al, 2008). In addition to c-H2AX formation after many types of DNA damage, we and other researchers are convinced that c-H2AX detection provides a considerably more sensitive and convenient measurement of DNA damage than other techniques such as pulse field gel electrophoresis and comet assays (Mah et al, 2010;Toyooka and Ibuki, 2006;Toyooka et al, 2011).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
See 2 more Smart Citations
“…The repair of these types of damage also induce c-H2AX (Bonner et al, 2008). In addition to c-H2AX formation after many types of DNA damage, we and other researchers are convinced that c-H2AX detection provides a considerably more sensitive and convenient measurement of DNA damage than other techniques such as pulse field gel electrophoresis and comet assays (Mah et al, 2010;Toyooka and Ibuki, 2006;Toyooka et al, 2011).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
“…We previously reported that phosphorylation of histone H2AX (c-H2AX) is a good marker for several types of DNA damage (Toyooka and Ibuki, 2006;Toyooka et al, 2011). c-H2AX was originally identified as an early event after the direct formation of DNA double-strand breaks (DSBs) (Rogakou et al, 1998).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that ␥-H2AX is generated following the exposure of cells to various suspected DNA-damaging agents including several environmental chemicals and pharmacological agents [20][21][22][23][24][25][26][27][28]. In addition to the advantage that ␥-H2AX can be detected in response to many types of DNA damage, we and other researchers are convinced that ␥-H2AX provides a considerably more sensitive measurement of DNA damage than other techniques such as pulse field gel electrophoresis and comet assays [26][27][28][29]. Therefore, focusing on ␥-H2AX as a genotoxic marker is a good way to identify the genotoxic potential of environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Foi demonstrado a co-localização de pH2AX inclusive com outras proteínas sinalizadoras de dano de DNA, como ATM e Rad51 em focos de dano de DNA após exposição à radiação ultravioleta (Oh et al, 2011;Toyooka et al, 2011).…”
Section: Danos Ao Dnaunclassified